Formulasi Masker Peel-Off Ekstrak Biji Buah Pepaya (Carica papaya L.) Sebagai Antijerawat dengan Variasi Konsentrasi Polivinil Alkohol - Vina Purnamasari M; Aztriana Aztriana; A Hasrawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Papaya seeds have the ability to an antibacterial because they contain triterpenoid compounds, papain enzymes, and fatty acids such as oleic acid, palmitic acid, and linoleic acid which can moisturize the skin and shed dead skin cells so that they are suitable for making peel-off masks. The study aimed to obtain a peel-off mask formulation of papaya seed extract (Carica papaya L.) as a stable anti-acne and has good pharmaceutical properties. The research design used was laboratory experimental research. Papaya fruit seed extract peel-off masks are made in 2 formulas with variations in PVA concentrations, namely 10% and 12%. The peel-off masks obtained were tested for stability including organoleptic testing, homogeneity, viscosity, dispersion ability test, pH test, drying speed test, and primary irritation test. The results showed that papaya fruit seed extract can be made into a peel-off mask formula that meets the pharmaceutical stability test, but formula 2 shows the most optimal stability and good pharmaceutical properties compared to formula 1. In addition, the two formulas do not irritate the skin so they are safe to use when applied.